2007
DOI: 10.1164/rccm.200608-1109oc
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis Infection Treatment and T-Cell Responses to Mycobacterium tuberculosis–specific Antigens

Abstract: LTBI treatment had a differential effect on T-cell responses to ESAT-6 and CFP-10 as measured by the T-SPOT.TB. The quantitative response to CFP-10 may be a useful LTBI treatment-monitoring tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
112
4
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 23 publications
11
112
4
2
Order By: Relevance
“…In the present study, the reversion rate of QFT-IT was high (81 ) in patients completing IPT, while reversion were not detected in those without IPT. The reversion rate was higher than those reported in either the HIV-infected persons of the Norwegian study (23 ; 15) or the non-HIV-infected cohort (5-42 ) (11,13,14,(18)(19)(20). The higher reversion rate in our study than in the Norwegian study could be because of our higher rate of compliance to LTBI treatment, lower median IFN-γ baseline level (1.05 IU mL vs. 3.48 IU mL), and a higher proportion of patients completing serial QFT-IT testing (95 vs. 52 ) enabling more accurate assessment of IFN-γ responses.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…In the present study, the reversion rate of QFT-IT was high (81 ) in patients completing IPT, while reversion were not detected in those without IPT. The reversion rate was higher than those reported in either the HIV-infected persons of the Norwegian study (23 ; 15) or the non-HIV-infected cohort (5-42 ) (11,13,14,(18)(19)(20). The higher reversion rate in our study than in the Norwegian study could be because of our higher rate of compliance to LTBI treatment, lower median IFN-γ baseline level (1.05 IU mL vs. 3.48 IU mL), and a higher proportion of patients completing serial QFT-IT testing (95 vs. 52 ) enabling more accurate assessment of IFN-γ responses.…”
Section: Discussioncontrasting
confidence: 67%
“…These findings suggest that frequent serial IGRA tests may be useful for monitoring IPT response, especially in cases where the drug resistance of M. tuberculosis is unknown. Other studies have reported similar responses of IFN-γ after LTBI treatment in both non-HIV-infected (11,13,14,18,19) and HIV-infected individuals (15). However, studies on non-HIV-infected patients have reported that the significant decrease of IFN-γ level occurred regardless of compliance to LTBI treatment (14,20).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although this would be a very important point in a public health programme, the data available today [78][79][80][81][82] are limited and : six out of nine patients developing tuberculosis were cultureconfirmed; two of them were negative by both IGRAs and, in one tuberculosis patient, culture-confirmed IGRA testing was not performed. mostly obtained with experimental techniques and in particular settings, making it difficult to interpret their potential clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the more encapsulated and quiescent the lesions and the smaller in size they are, the more likely it is that Th1 cell immunity will decline [18]. Indeed, a reversion from a positive to a negative tuberculin skin test can occur at a rate of 5%?yr -1 and there is evidence that IGRA positivity also wanes, and perhaps even more quickly, over time [30,31].…”
Section: Sectionmentioning
confidence: 99%